Perempuan dalam Kajian Sosiologi Gender: Konstruksi Peran Sosial, Ruang Publik, dan Teori Feminis - Maulida, Hanifa (Indonesian Democracy Research Center, 2021)
This article discusses women in the context of Gender Sociology, focusing on three main arenas. First, it examines the social construction of gender roles between women and men in society, particularly within the Indonesian context. Second, it explores how the public sphere perceives women, and third, it analyzes women through various feminist theoretical perspectives. To elaborate on these three arenas, the author employs a literature-based approach, producing theoretical and cumulative descriptions rather than empirical findings. The results of this study reveal three key insights. First, gender differences between men and women are socially constructed rather than naturally given; they emerge through processes of socialization involving values, norms, and cultural practices that are both transmitted and reinforced by society. Second, the public sphere is understood more broadly as a domain beyond domestic activities that have been socially constructed as women’s spaces, such as the kitchen, the well, and the bed. Third, the discussion of feminist theories, including liberal feminism, radical feminism, cultural feminism, and socialist feminism, shows that each offers a distinct perspective on women’s position, status, and way of life.